Nyanyian dan Musik dalam Tinjauan Hadis Nabi (RIWAYAH, 2015)
This article will examine the problem of singing and music in the review of the hadith of the Prophet. Related to singing and music, the view of the scholars is quite diverse. Most people forbid it, some of them allowed it, and some others allowed it with some requirements. Based on the search for some of the traditions of the Prophet, the hadiths that talk about the singing and the music can be classified into two groups, namely the traditions that do not contain a ban on singing, music, musical instruments, or singers, and the traditions that contains a ban on singing, music, musical instruments, or singers. Given two conflicting groups of traditions, based on the method of al-jam’u wa at-taufiq, it can be concluded that singing, musical instruments, and a female singer (singer) is not at all forbidden by Islam as long as it doesn’t contradict to the Islamic norms. Conversely, if the singing, musical instruments and a female singer (singer) cause the growth of hypocrisy and wickedness, then forbidden and recommended to be shunned. Thus, the hadith about the ban on singing and music is merely temporal and limited by a number of requirements, which do not lead to neglect and forget God.